Lamenting the Loss versus the Fallacy of Extinct Literary Genres in World Literature - Mahfouz, Safi; Salam, Wael (Dirasat: Human and Social Sciences, 2021)
This article explores some ostensibly extinct literary genres in world literature. The theoretical thrust of this article is based on Mikhail Bakhtin’s concept of chronotope, Gregory Bateson’s concept “ecology of the mind”, and Hubert Zapf’s concept “literature as a cultural ecology.” The main objective of the article is to show whether literary genres really become extinct or rather integrate into others to be reborn or to give life to new genres. Regeneration, resurrection and rebirth are not germane to species, but are also inclusive of literary genres. This hypothesis would prove the fallacy of the extinction of literary genres in world literature. Just like animals, some literary genres become extinct and new ones emerge. The array of the seemingly extinct literary genres in world literature is huge, so the current study will be limited to discussing a handful of these genres as illustrative examples. Extinct literary genres include the epic, trilogies, classical tragedies, morality plays, shadow plays, the Arabic māqamāt, oral literature, ballads, odes, sonnets, the Japanese poetry "Haiku", the Chinese Shenmo “martial arts novels”, Zhiguai fiction “folkloric myths”, metaphysical poetry, confessional poetry, pastoral poetry, fairy tales, the Bildungsroman, diaries, memoires, and many others. The study shows that technology, modernization, globalization and people’s changing preferences have resulted in the alleged extinction of many outdated literary genres and the emergence of new genres such as screenplays, sitcoms, soap operas, movies and cyberspace literature.